منهاج دعوة الشيخ محمد بن عبد الوهاب في كتاب التوحيد الذي هو حق الله على العبيد - Siti Rohmah; Husnul Khatimah (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2020)
Sheikh Muhammad bin Abdul Wahhab, may God have mercy on him, is a renewed reformer of the reformist preaching movement this era. Many people of common sense make up their hearts by this da’wah. And this blessed da’wa spread to many spots on the face of the earth because it was in the right curriculum. But this da’wa’s opponents mutilated it to prevent people from accepting it, Rather, they consider that the book of monotheism that the Sheikh wrote for the sake of his da’wa is the